SUMMARY OF SUBJECT MATTER FOR THE HEARING ON AIR LINER CABIN AIR QUALITY (Tufts Archival Research Center, 2007)
Memorandum from the House Aviation Staff to the Members of the Aviation Subcommittee discussing airliner cabin air quality for a legislative hearing. Reviews the history of efforts to improve air quality on airlines to improve health and safety flying conditions for both crew members and passengers. Focuses on issues involved in ensuring air quality, including the airplanes themselves, ventilation systems, environmental tobacco smoke, pesticides and specific contaminants such as carbon dioxide. Reports on specific legislation proposed for the purpose of ensuring safe air in airplane cabins (the Safe Cabin Air Quality Act).